2016
DOI: 10.1111/apa.13493
|View full text |Cite
|
Sign up to set email alerts
|

Pain and hospital admissions are important factors associated with quality of life in nonambulatory children

Abstract: Pain and hospital admissions were the most important factors that were negatively associated with HRQoL in nonambulatory children with CP between five to 18 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 33 publications
5
36
0
1
Order By: Relevance
“…A recent Dutch study of 66 non-walking children with CP also found that GMFCS V predicted low CPCHILD total score and low score on domain 1 (Elema et al. 2016). In that study, socioeconomic factors were included in addition to child characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Dutch study of 66 non-walking children with CP also found that GMFCS V predicted low CPCHILD total score and low score on domain 1 (Elema et al. 2016). In that study, socioeconomic factors were included in addition to child characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In addition to respiratory illnesses being the major contributor of premature death in people with CP, some also have recurrent respiratory illnesses which has a major impact on their quality of life. 5 Children and young people with CP also have a high rate of hospital admissions for respiratory illnesses. 6,7 Hospital care is also very costly.…”
mentioning
confidence: 99%
“…These repeated and lengthy hospital stays for respiratory illness represent a heavy burden for families. For children with CP, hospitalisation is one of the major factors impacting on health-related quality of life 3. Twenty-one ICD-10 diagnostic codes were recorded for these 98 admissions.…”
mentioning
confidence: 99%